Direct oral anticoagulants toxicity in children: an overview and practical guide. Issue 9 (2nd September 2022) - Daei, Maryam; Abbasi, Golnaz; Khalili, Hossein; Heidari, Zinat
ABSTRACT: Introduction: By increasing use of direct oral anticoagulants (DOACs) in adults and children, gradual increase in the number of intentional or unintentional DOAC poisonings among children is suspected in the near future. Hence, clinicians and pharmacists need to be familiar with the clinical features and management of DOAC-toxicity among pediatric population. Areas covered: This article provides an overview and practical guide to DOAC-toxicity in pediatrics according to the available clinical evidence. Expert opinion: Based on limited available data, accidental pediatric ingestion of DOACs can be managed by supportive care in most cases. However, serious toxicity may occur following massive overdose, in presence of underlying disorders (renal or hepatic dysfunction) and concurrent anticoagulant therapy. Activated charcoal is recommended for known recent ingestion of DOACs (within 2–4 hours) to reduce the gastrointestinal absorption. Supportive interventions including local hemostatic measures and volume resuscitation are the cornerstone of management of bleeding. Vitamin K and fresh frozen plasma are ineffective for DOAC reversal and thus are not recommended. Currently, safety and efficacy data regarding the use of specific reversal agents (including idarucizumab and andexanet alfa) and 3-factor or 4-factor prothrombin complex concentrate (PCC) or activated PCC (aPCC) among children with DOAC-associated bleeding are lacking.